Developing Social Learning Theory–Based Counseling with Godril Dance Values to Reduce Negative Peer Influence in Students’ Qur'an Memorization - Muhammad Hasan Syaifuddin; Mudafiatun Isriyah; Dewi Masyitoh (Kuras Institute, 2026)
Qur’an memorization programs in Islamic schools play an important role in developing students’ intellectual and spiritual balance. However, the consistency of students in memorizing the Qur’an is often influenced by social interaction dynamics, particularly negative peer influence that may reduce motivation and discipline in memorization activities. This study aims to develop and examine the feasibility of a Counseling Guidance module based on Social Learning Theory (SLT) integrated with the local cultural values of Tari Godril as a strategy to reduce negative peer influence among Tahfidz students at MAN Lumajang. The study employed a Research and Development (R&D) approach using the ADDIE model which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were Tahfidz students of class X-C at MAN Lumajang who participated in small group trials and field trials. Data were collected through observations, interviews, documentation, expert validation questionnaires, and student response questionnaires. The results of expert validation indicated that the module was categorized as very valid with material feasibility of 88%, language feasibility of 85%, design feasibility of 84%, and practicality of use by practitioners of 90%. Students’ responses to the developed module also showed a very positive category with an average percentage of 86.25%. The integration of Social Learning Theory with the philosophical values of Tari Godril strengthens the contextual relevance of counseling services within the cultural environment of the students. These findings confirm that the developed counseling module is feasible to implement as an innovative counseling strategy to help Tahfidz students manage negative peer influence and maintain consistency in memorizing the Qur’an.